2017
DOI: 10.1111/tme.12395
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of positive and false‐positive results in syphilis screening of blood donors in Rio de Janeiro, Brazil

Abstract: CLIA represents an improvement in blood bank serological screening. However, its use in a healthy population appears to result in high rates of false positives. Identifying which characteristics can predict false positives, however, remains a challenge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 19 publications
1
4
1
2
Order By: Relevance
“…This study is the largest single study of syphilis BFP test results. Like previous studies, we found that 11% of reactive nontreponemal tests were BFPs, and most had low-titers (7,8,15). About 1% of the BFPs were high-and very high-titer BFPs, and 4-fold titer increases in individuals with only BFP syphilis results were not uncommon.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…This study is the largest single study of syphilis BFP test results. Like previous studies, we found that 11% of reactive nontreponemal tests were BFPs, and most had low-titers (7,8,15). About 1% of the BFPs were high-and very high-titer BFPs, and 4-fold titer increases in individuals with only BFP syphilis results were not uncommon.…”
Section: Discussionsupporting
confidence: 84%
“…Studies of BFPs have been based on general population syphilis testing, which identified a few hundred BFPs, or testing of specific populations with even fewer BFPs (6,8,9,12,14). These studies found that most BFPs have low titers (Յ1:4), and the nontreponemal tests often revert to nonreactive without intervention (7,15). The largest general population study is from a university hospital, where testing of 300,000 serum samples yielded 726 BFPs with titers of Ն1:4, including 86 BFPs with titers of Ն1:32 (16).…”
mentioning
confidence: 99%
“…En relación a las serologías reactivas para enfermedad de Chagas también la prevalencia encontrada fue similar a otros estudios (4,13,19,20) . Esta enfermedad es endémica en el Paraguay y muchas de las personas son asintomáticas.…”
Section: Resultsunclassified
“…Un estudio realizado en Brasil encontró asociación entre la edad de los donantes, nivel educativo y la serología reactiva para sífilis (13) . En otro estudio realizado en China existe asociación entre el antecedente familiar de infección, compartir algunos objetos personales y tratamiento dental con infección con el VHB (14) .…”
Section: Introductionunclassified
“…In two different studies reported from Brazil (15,16), the reverse algorithm involving the use of the CLIA method improved the results of blood bank serologic screening, but still resulted in a high rate of false positive results in a healthy population, such as blood donors, which continues to be a problem.…”
Section: Resultsmentioning
confidence: 99%